Influence of plant growth regulators on sex differentiation and floral characteristics of pomegranate flowers: a case of brassinosteroids - Zeliha Gokbayrak; Hakan Engin (Acta Societatis Botanicorum Poloniae, 2018)
The objective of the present study was to determine the effects of brassinosteroid application on the sex determination and floral growth of pomegranate flowers. Whole tress of Punica granatum ‘Mayhoş-8’ were sprayed with 0.001, 0.01, and 0.1 mg L−1 28-homobrassinolide (Hbr) at bud break. The selection of flowers was based on the appearance of a visible pistil/stigma and shape of the ovary of intact flowers. Grouping of bisexual flowers was based on their flower position, i.e., single, terminal, and lateral flowers, during the first flush of flowering in mid-June. Approximately 20 days and 40 days after spraying, 100 randomly chosen bisexual flowers per collection time were collected and measurements of floral parts were immediately taken. The differences between bisexual and functional male flowers were not distinct enough to assert any significant effects from the different Hbr treatments. Irrespective of treatments, the percentage of male flowers was higher than that of bisexual flowers. Hbr treatments applied at the bud break period had significant effects only on bisexual flowers that developed as single flowers. Applying 0.01 mg L−1 Hbr produced comparably lower percentages of single bisexual flowers (53.4%). Although the 0.1 and 0.001 mg L−1 Hbr treatments resulted in increased percentages of bisexual flowers, the difference was not significant. For the first collection time (mid-June), the effects of Hbr concentration on the size of the floral parts for bisexual flowers were only significant in ovary width and stigma diameter. As the concentration decreased, smaller ovaries were obtained. During the second flowering, application of 0.01 mg L−1 Hbr considerably increased the overall sizes of floral parts in bisexual flowers. Hbr might affect the ratio of flower formation in certain positions on a branch and could influence the growth of floral parts in bisexual flowers. Further elucidation of these effects would help to better understand floral organ development in plants.